From homo economicus to homo corporativus: a neglected critique of neoclassical economics - Bastien, Carlos (2009)
In the 1930s, the conventional neoclassical concept of economic man was subject to different kinds of criticism. One contribution that so far has not been consistently scrutinised was presented by the economic doctrine of corporatism, which was particularly influential in Southern European countries. This paper deals with the foundations of the corporatist doctrine during the inter-war period, exploring the relevance of the concept of homo corporativus as a new approach to the study of economic behaviour and the economic representation of human nature.